2002
DOI: 10.1300/j002v34n03_05
|View full text |Cite
|
Sign up to set email alerts
|

Richard A. Fabes, Department of Family & Human Development, Arizona State University, Tempe, AZ 85287-2502 (E-mail

Abstract: The Coping with Children's Negative Emotions Scale (CCNES) is an increasingly used self-report instrument consisting of six subscales that reflect different ways parents respond to their young children's negative emotions. However, psychometric testing of this scale has not been conducted. In two studies, we examine its psychometric properties. In the first study, 101 parents (mostly mothers) completed the CCNES and a variety of other scales. The results reveal that the CCNES is internally reliable and has sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
171
2
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(223 citation statements)
references
References 35 publications
9
171
2
11
Order By: Relevance
“…Multiple studies in different cultures reported CCNES as a valid and reliable measure for assessing mothers' responses to children's negative emotions (e.g., Altan-Aytun, Yagmurlu, & Yavuz, 2013;Fabes et al, 2002). Several studies have replicated a two-factor structure (i.e., supportive and unsupportive reactions) of this measure (e.g., Davidov & Grusec, 2006;.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies in different cultures reported CCNES as a valid and reliable measure for assessing mothers' responses to children's negative emotions (e.g., Altan-Aytun, Yagmurlu, & Yavuz, 2013;Fabes et al, 2002). Several studies have replicated a two-factor structure (i.e., supportive and unsupportive reactions) of this measure (e.g., Davidov & Grusec, 2006;.…”
Section: Methodsmentioning
confidence: 99%
“…The Coping with Children's Negative Emotions Scale (CCNES; Fabes et al, 2002) was used to assess mothers' beliefs about how they respond to their own children's negative emotions. The CCNES assesses the degree to which a mother believes in encouraging emotion expression and whether she adopts emotion-or problem-focused responses.…”
Section: Interview Componentsmentioning
confidence: 99%
“…Emotion-focused behavior included strategies to help the child to feel better (e.g. comforting, distraction; Fabes et al, 2002).…”
Section: Interview Componentsmentioning
confidence: 99%
“…Recent studies have explored individual and family characteristics that could be related to the development of children's understanding of emotions (ToM-emotions) (Fabes, Poulin, Eisenberg, & Madden-Derdich, 2002;Labounty, Wellman, Olson, Lagattuta, & Liu, 2008;McElwain, Halberstadt, & Volling, 2007). These studies have emphasized the importance of understanding a) how parents react to their children's emotions, b) how they talk about emotions, and c) how they express their emotions themselves, in order to explore how they contribute to their children's emotional competences.…”
Section: Introductionmentioning
confidence: 99%
“…This study focused specifically on mothers' and fathers' reactions to positive and negative emotions (PE and NE) expressed by their children. As most authors differentiate between supportive reactions (SR) and non-supportive reactions (NSR) (e.g., Eisenberg, Fabes, & Murphy, 1996;Fabes et al, 2002;Jones, Eisenberg, Fabes, & MacKinnon, 2002;McElwain et al, 2007;Pears & Moses, 2003) (see Table 1), we investigated these two types of reactions in each parent to PE and NE felt by their child.…”
Section: Introductionmentioning
confidence: 99%